The Development of Institutions for Serbia Organic Food Market Considering the Accession to EU - Sudarevic, Tomislav (Theory, Methodology, Practice – Review of Business and Management, 2011)
Within the food and beverages products category, organic food products are one of the most competitive markets in the EU today. Therefore, this paper discusses current features of the organic food scene in EU and in Serbia. Following that, alternative scenarios for entrance with organic food “Made in Serbia” into the EU market are elaborated. The first of them is inclusion on the Third Countries List as a long-term project. The second approach, joint co-certification, is easier to apply, with the first steps already done. The third scenario is based on acquiring certificates by contractual relationship with EU accredited certification organizations.